An improved reversible image watermarking algorithm based on difference expansion - Zhengwei Zhang; Lifa Wu; Yunyang Yan; Shaozhang Xiao; He Sun (International Journal of Distributed Sensor Networks, 2017)
To improve the visual quality and the embedding rate of the existing reversible image watermarking algorithm, an improved reversible image watermarking algorithm based on difference expansion is proposed. First, the watermark information is divided into groups, and the information value of each group is calculated. The watermark group number and the corresponding carrier image block number are mapped, and the corresponding coefficient position of each corresponding carrier block is identified according to the value of the watermark information in each group. Second, the identified location map is compressed and embedded in the original image through the difference expansion. Through circular searching the suitable pixel position, the embedding rate can be effectively improved without sacrificing any visual quality. The experimental results show that the proposed algorithm not only has high embedding rate but also has a high visual quality and can achieve full recovery of the original image. Compared with other algorithms, the algorithm has certain advantages.